The Validity of Using E4D Compare's "% Comparison" to Assess Crown Preparations in Preclinical Dental Education. Issue 12 (1st December 2015) - Callan, Richard S.; Van Haywood, B.; Cooper, Jeril R.; Furness, Alan R.; Looney, Stephen W.
Abstract : When a dental school is deciding which technology to introduce into a curriculum, it is important to identify the educational goals for the system. The authors' primary goal for the use of a computer‐aided resource was to offer students another way to assess their performance, to enhance their learning, and to potentially decrease their learning curve in the preclinical environment prior to using the technique in clinical patient care. The aim of this study was to examine the validity of the "% Comparison" numbers derived from the E4D Compare software program. Three practical examinations were administered to a class of 82 students at one U.S. dental school over a six‐week period. The grading of the practical examinations was performed with individual faculty members being responsible for evaluating specific aspects of each preparation. A digital image of each student's practical examination tooth was then obtained and compared to the digital image of an ideal preparation. The preparations were compared, and the "% Comparison" was recorded at five tolerance levels. Spearman's correlation coefficient (SCC) was used to measure the agreement in rankings between the faculty scores on practical exams 1–3 and the scores obtained using E4D Compare at the different tolerance levels. The SCC values for practical exams 2 and 3 were all between 0.2 and 0.4; for practical exam 1, the SCC values ranged from 0.47 to 0.56. There was no correlation between the faculty scores and the numbers given by the "% Comparison" of the software.